Transfusion- Associated Graft vs Host Disease in a Post-Coronary Artery Bypass Graft Patient - Saba, Sayedatus; Tabassum, Noshin; Kamal, Mohammed; Khalequzzaman, Md.; Islam, Md. Mazharul; Billah, Md. Mustain (Journal of Medical Health Research and Psychiatry, 2024)
TA-GVHD is a rare, usually fatal complication of transfusion of blood and blood products containing viable T lymphocytes. Very rarely it may arise in an immunocompetent individual. There is an increased risk of TA-GVHD following bypass grafting and other surgical procedures where blood transfusion are required. Here we present a case of a 57 old patient who received 5 units of whole blood from his close relatives perioperatively and manifested unexplained anaemia, fever, skin rash which later became desquamating & cheilitis on his 19th POD. His CBC report suggested pancytopenia indicating bone marrow failure. Skin biopsy confirmed the diagnosis as chronic TA-GVHD, lichenoid type. His liver function deteriorated and he died subsequently on his 32nd POD. TA-GVHD develops when immunocompetent T lymphocytes of transfused blood able to engraft in the recipient’s lymphoid tissues that fail to reject them. Those lymphocytes mediate immune response causing damage and dysfunction of the skin & other organs. Our patient showed all features of TA-GVHD that was complicated by sepsis and multiorgan failure despite aggressive management. Pathologists, surgeons, physicians and transfusion centers must be aware of this sinister complication of perioperative blood transfusion in any surgery, including CABG. Though fatal in >90% cases, it can be prevented by using irradiated blood. Patient parties must also be discouraged to donate blood to avoid this grave outcome.